Percentage occurrence of global tilted deep convective clouds under strong vertical wind shear. Issue 6 (15th March 2022) - Sharma, Neerja; Kumar Varma, Atul; Liu, Guosheng
Highlights: Rainfall measurement is always inconclusive if the structure of cloud is tilted. Vertical wind shear a solely factor for cloud tilt is rarely examined. Globally 60.68% of deep convective clouds are developed in strong wind shear. These deep convective clouds produced intense rain > 50 mm/hr. Need to develop correction procedures for rain estimation from tilted clouds. Abstract: The percentage occurrence of titled deep convective clouds (DCCs) is rarely examined but it is crucial to overcome the challenges of precise measurement of rainfall intensity and location during dreadful weather events. Present study is carried out with this objective and analysed 2451 globally distributed DCCs identified by Ku-band (13.6 GHz) radar reflectivity profiles of Dual-frequency Precipitation Radar aboard Global Precipitation Measurement mission under varying conditions of environmental vertical wind shear (EVWS) during 2018. Globally (tropics) 60.68% (55.29%) of DCCs that produced intense rain (>50 mm/hr) are strengthened under strong EVWS and thus may have possibility of vertically tilted structure. Substantial 60.49% of DCCs that developed under strong EVWS grow deeper (up to 12 km) in atmosphere. Statistics on the global distribution of DCCs developed in strong EVWS with different categories of rainfall and cloud height would be an important source of information for precise assessment of rainfall distribution, especially during extreme weather.